Terminologia da ourivesaria no município de Abaetetuba-PA - SILVA, Júlia Rita Ferreira da (2019)
This work is based on the construction of a glossary of the linguistic terms of jewelery, using as theoretical reference The Sciences of the Lexicon - Lexicography, Lexicology and Terminology - with focus on the Terminology for the study of the terms of this community that is being analyzed, according to the authors Faulstich (2001), Cabré (1999), Biderman (2001), Pavel (2002) and Krieger and Finatto (2004). The study was developed from the application of the Lexical Semantic Questionnaire (LSQ), elaborated in the discipline, Introduction to Terminology, of the course of Letters. However, going to the field was extremely important in order to extract the greatest number of terms, contextualizing and illustrating the presented items. The LSQ was applied to three informants, in the city of Abaetetuba, in three different production units. Through this, it was possible to obtain as a result an illustrated glossary with 61 terminological items, being contextualized by an ethnographic narrative. It's hoped that this work can offer a greater visibility to the lexicon of this community, considering fundamentally the cultural richness peculiar to it.